NiGa Unsupported Catalyst for CO2 Hydrogenation at Atmospheric Pressure. Tentative Reaction Pathways - Cortés-Reyes, Marina; Azaoum, Ibrahim; Molina-Ramírez, Sergio; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; Alemany-Arrebola, Luis José (American Chemical Society, 2021)
The hydrogenation of CO2 is presented as a catalytic strategy for CO2 utilization and an approach to the development of sustainable processes to obtain products with high added value, such as CO, CH4, and CH3OH. An unsupported NixGay model catalyst with high surface area was synthesized by an ultrasonic-assisted coprecipitation method. The in situ H2-treatment and the activation temperature (600, 700, and 800 °C) are key in the phases present in the catalyst and, therefore, in the reactivity in the CO2 hydrogenation reaction at atmospheric pressure. Operating conditions have been selected that maximize the selectivity to be able to correlate phases, surface, and reactivity. Independently of the H2/CO2 feed ratio, after treatment in hydrogen at 600 °C, CO selectivity values are higher than 97%, via a reverse water gas shift reaction, with Ni13Ga9 and Ni metallic being the main phases detected. The H2-treatment at 700 °C increases the proportion of Ni0 and Ni13Ga9 phases, and even with the use of a H2/CO2 feeding ratio of 3, methanation is the only reaction that occurs. At 800 °C, Ni5Ga3 is the main phase detected, and methanol is formed at 150 °C, through the intervention of a necessary formate species; when the reaction temperature is higher than 400 °C, the rWGS is the only observable reaction, with complete CO formation.
Keywords: Catalizadores; Alcohols; Catalysts; Chemical reactions; Hydrogen; Oxides